A Computational Fluid Dynamic Study of Developed Parallel Stations for Primary Fans - Hurtado-Cruz, J; Vargas-Norambuena, J (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
A Computational fluid dynamic (CFD) model was developed considering three geometries for primary parallel fan stations that have already been developed, implemented, and are currently in operation within Chilean mines. To standardize the comparison, the same primary fan was used in all the simulations with a unique set of settings (speed, blade angle, and density). The CFD representation was used to determine the operating point per configuration and compare the performances in terms of airflow and pressure delivered. This approach allowed ranking primary fan station geometry based on resistance curve and energy consumption of the fan. This paper presents the results obtained through the CFD simulations and the corresponding primary fans operating points of each configuration: symmetrical branches (SB), overlap branches (OB), and run around (RA) bypass. The RA configuration was identified as the best-performing station geometry on the lowest frictional and shock pressure losses, highest airflow delivery, and lowest energy cost. The results are discussed, considering pressure, velocity, and vector contours to understand the fluid dynamics phenomena occurring inside the station. The capital cost involved in the development of each primary parallel station was considered in the analysis in addition to the energy cost to determine the economic configuration over time. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.